Analisa Studi Kelayakan Ekonomis Penambangan dan Kebutuhan Alat Penambangan Batubara di Pit IV PT. Tambang Bukit Tambi site Padang Kelapo, Kabupaten Batanghari, Provinsi Jambi - Gerry Vernando; Sumarya Sumarya; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT.Tambang Bukit Tambi is a company that will plan coal mining in Semambu Village, Sumay Subdistrict, Tebo District, an investment analysis and economic feasibility of the mine are needed to see the prospect of coal reserves in that location. Reference to the preparation of the economic model used is based on investment costs, production costs, and revenues from coal sales.To consider this, an economic feasibility analysis is needed. The parameters used to determine the economic feasibility of the coal production plan of PT. Tambang Bukit Tambi is Net Present Value (NPV), Internal Rate of Return (IRR) , Payback Period (PBP).The total reserves in pit 4 PT. Tambang Bukit Tambi is 240.000 tons, with an overburden volume of 20.000bcm .Based on the amount of available reserves for coal getting and stripping activities OB, the number of loading and unloading equipment and transportation planned up to 2024 is 1 unit of Excavator Komatsu PC 400 and 3 units of Dump Truck Komatsu 220 and for 2025 until 2033 for coal getting and stripping activities OB is needed tool transport of 4 units of Articulated Dump Truck Volvo A40E .The results of the investment analysis of the feasibility of the mining plan of PT. Tambang Bukit Tambi gets total numbers the profit earned is. The feasibility of mining investment plans is obtained by a positive NPV of Rp. 455.157.523.160,00, an IRR value of 31,4 % with a MARR 6.5% and a payback period obtained at 3.002 years.Keywords: feasibility, invesment, NPV, IRR, Payback Period